Seed coat development in explosively dispersed seeds of Cardamine hirsuta. (4th December 2019) - Neumann, Ulla; Hay, Angela
Abstract: Background and Aims: Seeds are dispersed by explosive coiling of the fruit valves in Cardamine hirsuta . This rapid coiling launches the small seeds on ballistic trajectories to spread over a 2 m radius around the parent plant. The seed surface interacts with both the coiling fruit valve during launch and subsequently with the air during flight. We aim to identify features of the seed surface that may contribute to these interactions by characterizing seed coat differentiation. Methods: Differentiation of the outermost seed coat layers from the outer integuments of the ovule involves dramatic cellular changes that we characterize in detail at the light and electron microscopical level including immunofluorescence and immunogold labelling. Key Results: We found that the two outer integument (oi) layers of the seed coat contributed differently to the topography of the seed surface in the explosively dispersed seeds of C. hirsuta vs. the related species Arabidopsis thaliana where seed dispersal is non-explosive. The surface of A. thaliana seeds is shaped by the columella and the anticlinal cell walls of the epidermal oi2 layer. In contrast, the surface of C. hirsuta seeds is shaped by a network of prominent ridges formed by the anticlinal walls of asymmetrically thickened cells of the sub-epidermal oi1 layer, especially at the seed margin. Both the oi2 and oi1 cell layers in C. hirsuta seeds are characterized by specialized, pectin-rich cell walls that are deposited asymmetrically in the cell. Conclusions: The two outermost seed coat layers in C. hirsuta have distinct properties: the sub-epidermal oi1 layer determines the topography of the seed surface, while the epidermal oi2 layer accumulates mucilage. These properties are influenced by polar deposition of distinct pectin polysaccharides in the cell wall. Although the ridged seed surface formed by oi1 cell walls is associated with ballistic dispersal in C. hirsuta, it is not restricted to explosively dispersed seeds in the Brassicaceae.